Two divergent paths: compression vs. non-compression in deep venous thrombosis and post thrombotic syndrome - Da Matta, Eduardo Simões (Jornal vascular brasileiro, 2017)
Abstract Use of compression therapy to reduce the incidence of postthrombotic syndrome among patients with deep venous thrombosis is a controversial subject and there is no consensus on use of elastic versus inelastic compression, or on the levels and duration of compression. Inelastic devices with a higher static stiffness index, combine relatively small and comfortable pressure at rest with pressure while standing strong enough to restore the “valve mechanism” generated by plantar flexion and dorsiflexion of the foot. Since the static stiffness index is dependent on the rigidity of the compression system and the muscle strength within the bandaged area, improvement of muscle mass with muscle-strengthening programs and endurance training should be encouraged. Therefore, in the acute phase of deep venous thrombosis events, anticoagulation combined with inelastic compression therapy can reduce the extension of the thrombus. Notwithstanding, prospective studies evaluating the effectiveness of inelastic therapy in deep venous thrombosis and post-thrombotic syndrome are needed. Resumo O uso da terapia de compressão para reduzir a incidência de síndrome pós-trombótica em pacientes com trombose venosa profunda apresenta controvérsias como o uso da compressão elástica versus inelástica, os níveis e a duração da compressão. Dispositivos inelásticos com índice de rigidez estática combinam uma pressão pequena e confortável em repouso com uma pressão forte o suficiente para restaurar o “mecanismo de válvula” gerado pela flexão plantar e dorsiflexão do pé. Uma vez que o índice de rigidez estática depende da rigidez do sistema de compressão e da força muscular dentro da área enfaixada, a melhoria da massa muscular com programas de fortalecimento e treinamento de resistência deve ser incentivada. Na fase aguda dos eventos de trombose venosa profunda, a anticoagulação acompanhada de terapia de compressão inelástica pode reduzir a extensão do trombo. Assim, são necessários estudos que avaliem a eficácia da terapia inelástica na trombose venosa profunda e na síndrome pós-trombótica.